Clinical significance of long noncoding RNA VIM‐AS1 and CTBP1‐AS2 expression in type 2 diabetes. Issue 6 (3rd December 2018) - Erfanian Omidvar, Maryam; Ghaedi, Hamid; Kazerouni, Faranak; kalbasi, Saeid; Shanaki, Mehrnoosh; Miraalamy, Ghasem; Zare, Ali; Rahimipour, Ali
Abstract: Background/Aims: The risk of type 2 diabetes (T2D) is determined by a combination of genetic and environmental factors. Multiple studies have proposed that long noncoding RNAs (lncRNAs) are crucial molecules in regulating several biological processes and complex diseases. The study was aimed at investigating the association between the expression levels of lncRNA VIM‐AS1, lncRNA CTBP1‐AS2, and T2D susceptibility. Methods: lncRNA VIM‐AS1 and lncRNA CTBP1‐AS2 in the peripheral blood mononuclear cell (PBMC) of 100 healthy individuals and 100 T2D patients were collected for Quantitative Real‐Time RT‐PCR analysis. A logistic regression was performed to understand whether the likelihood of T2D can be predicted based on the expression levels of lncRNA VIM‐AS1 and lncRNA CTBP1‐AS2. Receiver operating characteristic (ROC) analysis was also performed to determine the statistical analysis of VIM‐AS1 and CTBP1‐AS2 levels in 200 samples. Results: Our results display that decreased levels of VIM‐AS1 and CTBP1‐AS2 in PBMC were associated with diabetes in Iranian population. The logistic regression revealed that Systolic blood pressure (SBP), low‐density lipoprotein cholesterol (LDL‐C), Fasting blood glucose (FBG) and CTBP1‐AS2 are substantial predictors of T2D. The ROC analysis of CTBP1‐AS2 revealed the area under the ROC curve (AUC) of 0.68 with a sensitivity of 58.7% and specificity of 75.3% in distinguishing nondiabetic from diabetic subjects. The ROC analysis of VIM‐AS1 determined AUC of 0.63 with a sensitivity of 56.1% and specificity of 68.37% in distinguishing the two diagnostic groups. Conclusion: lncRNA VIM‐AS1 and lncRNA CTBP1‐AS2 expression levels are associated with T2D susceptibility. Abstract : The study was aimed at investigating the association of the expression levels of lncRNA VIM‐AS1 and CTBP1‐AS2 in the peripheral blood mononuclear cell (PBMC) with T2D susceptibility. Our results display that decreased levels of VIM‐AS1 and CTBP1‐AS2 in PBMC were associated with diabetes.